2015
DOI: 10.1002/jbio.201500176
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aqueous pollen extracts using surface enhanced Raman scattering (SERS) and pattern recognition methods

Abstract: Aqueous pollen extracts of varying taxonomic relations were analyzed with surface enhanced Raman scattering (SERS) by using gold nanoparticles in aqueous suspensions as SERS substrate. This enables a selective vibrational characterization of the pollen water soluble fraction (mostly cellular components) devoid of the spectral contributions from the insoluble sporopollenin outer layer. The spectra of the pollen extracts are species-specific, and the chemical fingerprints can be exploited to achieve a classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 35 publications
5
56
0
Order By: Relevance
“…Vibrational studies of pollen, by diverse infrared and Raman techniques, have shown that vibrational spectroscopy achieves economical and rapid identification and classification of pollen according to taxonomy and phylogenetic relationship (Pappas et al, 2003;Ivleva et al, 2005;Gottardini et al, 2007;Schulte et al, 2008;Dell'anna et al, 2009;Zimmermann, 2010Zimmermann, , 2018Guedes et al, 2014;Zimmermann and Kohler, 2014;Zimmermann et al, 2015b;Julier et al, 2016;Seifert et al, 2016;Woutersen et al, 2018;Jardine et al, 2019;Mondol et al, 2019). For example, the recent FTIR microspectroscopy study on individual pollen grains has achieved more accurate classification than optical microscopy, which is the benchmark method in pollen identification (Zimmermann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational studies of pollen, by diverse infrared and Raman techniques, have shown that vibrational spectroscopy achieves economical and rapid identification and classification of pollen according to taxonomy and phylogenetic relationship (Pappas et al, 2003;Ivleva et al, 2005;Gottardini et al, 2007;Schulte et al, 2008;Dell'anna et al, 2009;Zimmermann, 2010Zimmermann, , 2018Guedes et al, 2014;Zimmermann and Kohler, 2014;Zimmermann et al, 2015b;Julier et al, 2016;Seifert et al, 2016;Woutersen et al, 2018;Jardine et al, 2019;Mondol et al, 2019). For example, the recent FTIR microspectroscopy study on individual pollen grains has achieved more accurate classification than optical microscopy, which is the benchmark method in pollen identification (Zimmermann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational spectroscopic methods, such as FTIR (Pappas et al, 2003;Gottardini et al, 2007;Dell'Anna et al, 2009;Julier et al, 2016;Depciuch et al, 2018;Jardine et al, 2019), Raman scattering (Ivleva et al, 2005;Schulte et al, 2008), and surface enhanced Raman scattering (SERS) (Sengupta et al, 2005;Seifert et al, 2016), as well as mass spectrometric methods (Krause et al, 2012;Lauer et al, 2018) can be applied to classify pollen according to taxonomic relationships based on molecular composition. Pollen spectra can also indicate changes in chemical composition according to genetic background and environmental influences (Zimmermann and Kohler, 2014;Zimmermann et al, 2017;Diehn et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS), in turn, gives very strong signals from pollen constituents that must interact with metal nanoparticles, i.e., the SERS substrate, and although it enables the investigation of less abundant molecular species, it has a high selectivity for specific classes of molecules. This can be the water-soluble pollen fraction, extracted in a facile way (Seifert et al, 2016) or the sporopollenin polymer after embedding the SERS nanoparticle substrate inside the nanoscopic cavities of the pollen shell (Joseph et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The germination conditions for pollen grains are easy to adjust , and, focusing on different histological features and different pollen species, a comparison of the effects of variations in growth conditions for one pollen species can be achieved. In previous work, our and other groups have shown that Raman spectroscopy can serve as a method to characterize pollen grains under varying conditions , to image their biochemical composition , and to investigate the process of germination .…”
Section: Introductionmentioning
confidence: 99%